A PREHISTORIC JOURNEY TO THE CENTER OF THE EARTH : A GRAPHIC NOVEL - Harper, Benjamin; Frampton, Otis (North Mankato, Minnesota : Stone Arch Books, an imprint of Capstone, 2022)
In this version of the Jules Verne classic, Mateo, a young velociraptor, finds a puzzling artifact on his class's archaeological dig, which his famous uncle, Dr. Raptor, declares is a clue to the disappearance of the scientist, Ernie Stegosaur; the Doctor, his lab assistant, Darby, and Mateo follow the clue to the center of the Earth and discover a strange civilization--inhabited by creatures called human beings.
Keywords: Velociraptor -- Comic books, strips, etc; Velociraptor -- Juvenile fiction; Antiquities -- Comic books, strips, etc; Velociraptor -- Juvenile fiction; Explorers -- Comic books, strips, etc; Explorers -- Juvenile fiction; Graphic novels; Comics (Graphic works); Action and adventure comics